The Jakarta Dialect as a Lingua Franca in Indonesian Gaming Communities: A Sociolinguistic Study - Errando Varel; Samangilailai, Rofnal; Afian, Alvin; Rangkuti, Rahmadsyah (LPPM STKIP PGRI Bandar Lampung, 2025)
This study investigates the sociolinguistic role of the Jakarta dialect, especially features like lo and gue, within Indonesian online gaming communities. Although Indonesia is linguistically diverse, preliminary findings from related research such as the study on language and identity in online gamer communities. Meanwhile, recent work on digital dialect and regional variation shows hybrid phrases combining English and local idioms are used, but when speaking in voice chats or informal conversation, Jakarta dialect often dominates. Drawing on Fishman’s domain theory, Labov’s prestige framework, and Holmes’s identity solidarity construct, this paper explores how language choice in gaming enables gamers from different regions to assert group identity and create solidarity. Data will be collected via chat-log screenshots, Discord interactions, and interviews with participants across multiple regional backgrounds. The study aims to elucidate how and why the Jakarta dialect becomes a lingua franca in these communities, and what this means for local dialect maintenance.